As propostas curriculares da disciplina de biologia para a rede estadual de ensino de S??o Paulo no per??odo 1968-2008 - Pataki, Edna Ferreira da Silva (2019)
This study had as object of study the curricular proposals of biology of the Secretariat of Education of the State of S??o Paulo. The documents analyzed were the Curriculum Guides for Teaching of 1975; the Curricular Proposal for Teaching biology: 2nd Degree of 1992; and the S??o Paulo State Curriculum: natural sciences and their technologies of 2011. The problem that guided our research can be presented as follows: How do the curricular documents address the discipline of biology? The objective of the research was to know how the documents present questions such as curricular unification, contents of biology, interdisciplinarity, contextualization. Our research itinerary involved the analysis of curricular documents produced by the State of S??o Paulo's Education Department (SEE / SP). The theoretical references of the research were based on Silva (2010), Apple (2006), Moreira (1989), Sacristan (2000) and Lima (2011). The research results show that the documents present similarity, mainly because they are prescriptive and directive. Teacher subsidies, present in the curriculum proposals of 1968 and 1986, were replaced by the teacher's notebook, in the current proposal. The bibliography consulted shows that the critique of teachers to the present curriculum derives more from the process of its elaboration, which did not count on the teachers, than from the proposal itself. Our observation in everyday school shows that the teacher's difficulties in working on the current proposal derives from the enormous distance it projects and the objective conditions of students, teachers and school.